Penentuan Faktor Permintaan Perumahan di Temerloh Pahang - Nurul Firzana Azman; Kasim, Rozilah (Research in Management of Technology and Business, 2024)
The main goal of the national housing policy is to provide affordable housing facilities for buyers from various backgrounds and income levels. Nevertheless, the main issue is the mismatch of housing needs and demands. In addition, there is no specific measurement model to measure the factors affecting housing demand. Therefore, this study measures the factors that influence housing demand and determines the most significant factors affecting housing demand by buyers. This study uses a quantitative approach through the distribution of questionnaires to prospective buyers and tenants from the B40 income group in Mukim Perak, Temerloh Pahang. The data obtained is analysed using SPSS software. The findings showed the most significant factors and factors affecting the demand for housing in the study area. The results would be reference to future developers, buyers, tenants and researchers.